Does National Culture Impact Capital Budgeting Systems? - Peter J. Graham; Milind Sathye (Australasian Accounting, Business and Finance Journal, 2017)
We examine how national culture impacts organisational selection of capital budgeting systems to develop our understanding of what influence a holistic formulation of national culture has on capital budgeting systems. Such an understanding is important as it would not only provide a clearer link between national culture and capital budgeting systems and advance extant literature but would also help multinational firms that have business relationships with Indonesian firms in suitably designing strategies. We conducted semi-structured interviews of selected finance managers of listed firms in Indonesia and Australia. Consistent with the contingency theory, we found that economic, political, legal and social uncertainty impact on the use of capital budgeting systems. The levels of uncertainty were higher in Indonesia than Australia and need to be reckoned in the selection of capital budgeting systems used by firms. We also found that firms are influenced by project size and complexity, when selecting capital budgeting systems.
Keywords: Capital budgeting systems; National culture; Indonesia; Australia.